2021
DOI: 10.1016/j.ajpath.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Estrogen in Insulin Resistance

Abstract: Insulin resistance results when peripheral tissues, including adipose, skeletal muscle, and liver, do not respond appropriately to insulin, causing the ineffective uptake of glucose. This represents a risk factor for the development of type 2 diabetes mellitus. Along with abdominal obesity, hypertension, high levels of triglycerides, and low levels of high-density lipoproteins, insulin resistance is a component of a condition known as the metabolic syndrome, which significantly increases the risk of developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 84 publications
(128 reference statements)
1
30
0
4
Order By: Relevance
“…Both age-related and surgically induced menopause increase insulin resistance and the prevalence of other components of the metabolic syndrome [ 112 ]. These findings suggest the role of estrogen in the regulation of responsiveness to insulin [ 113 ]. However, the results of the studies evaluating the influence of HRT on glucose metabolism are not univocal which may be a consequence of methodological differences regarding the population selection, HRT type, and regimen as well as the timing of treatment initiation [ 114 ].…”
Section: Estrogens In the Regulation Of Adipose Tissue Metabolismmentioning
confidence: 99%
“…Both age-related and surgically induced menopause increase insulin resistance and the prevalence of other components of the metabolic syndrome [ 112 ]. These findings suggest the role of estrogen in the regulation of responsiveness to insulin [ 113 ]. However, the results of the studies evaluating the influence of HRT on glucose metabolism are not univocal which may be a consequence of methodological differences regarding the population selection, HRT type, and regimen as well as the timing of treatment initiation [ 114 ].…”
Section: Estrogens In the Regulation Of Adipose Tissue Metabolismmentioning
confidence: 99%
“…Male LVR also had significantly higher bodyweights relative to age-matched WT ( p = 0.031) ( Figure 6D ). This indicates that male LVR show signs of insulin resistance and obesity likely increasing their risk for AD while female LVR, relative to same-sex controls, were relatively unaffected potentially due to the protective effects of estrogen in the periphery ( de Paoli et al, 2021 ). We see very distinct effects of selecting for physical inactivity between male and female LVR in which female LVR primarily display significant deficits in brain health; whereas male LVR display systemic issues like insulin resistance and obesity yet are relatively spared from cognitive deficits.…”
Section: Resultsmentioning
confidence: 99%
“…There is compelling data in men that testosterone deficiency predisposed to MetS and in females that estrogen deficiency predisposes to an increase risk of MetS. 30 , 31 Furthermore studies have shown that sex hormone binding globulin (SHBG) also is an important determinant of MetS risk. 32 , 33 In future studies this important area needs to be investigated in relationship to insulin resistance and inflammation and dysbiosis of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%